2017
DOI: 10.1039/c7nr05085b
|View full text |Cite
|
Sign up to set email alerts
|

A general route to coat poly(cyclotriphosphazene-co-4,4′-sulfonyldiphenol) on various substrates and the derived N, P, S-doped hollow carbon shells for catalysis

Abstract: The construction of core-shell structures through surface coating, and then making use of the synergistic effects between the core and shell to design and synthesize heterogeneous catalysts is a hot topic in the heterogeneous catalysis field. Developing a general coating route with functional shell materials is further highly desirable. Here we found that a poly(cyclotriphosphazene-co-4,4'-sulfonyldiphenol) (PZS) layer can be generally coated on various substrates with different components and morphologies, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 97 publications
0
28
0
Order By: Relevance
“…As shown in Figure a,b, the ZIF‐67 polyhedron has a particularly rhombic dodecahedral morphology with well‐defined rhombus faces and average particle size of ≈750 nm. During the second step, the electrostatic interaction between the positively charged core (ZIF‐67) and the negatively charged PZS polymer, the coordination interaction between hexachlorocyclotriphosphazene (HCCP) and metal ions, as well as the hydrogen bond formed between 4,4′‐sulfonyldiphenol (BPS) and a N‐containing surface,[30a–d] all drive the adsorption of the monomers on the surface of ZIF‐67. Moreover, the in situ formed cationic surfactant triethylammonium chloride (TEA·HCl) promotes the dispersion of the positively charged ZIF‐67 core and also serves as electrostatic attractive points to improve the negatively charged PZS polymer deposited on cationic surfactant TEA + ‐modified cores [30a,e–g]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure a,b, the ZIF‐67 polyhedron has a particularly rhombic dodecahedral morphology with well‐defined rhombus faces and average particle size of ≈750 nm. During the second step, the electrostatic interaction between the positively charged core (ZIF‐67) and the negatively charged PZS polymer, the coordination interaction between hexachlorocyclotriphosphazene (HCCP) and metal ions, as well as the hydrogen bond formed between 4,4′‐sulfonyldiphenol (BPS) and a N‐containing surface,[30a–d] all drive the adsorption of the monomers on the surface of ZIF‐67. Moreover, the in situ formed cationic surfactant triethylammonium chloride (TEA·HCl) promotes the dispersion of the positively charged ZIF‐67 core and also serves as electrostatic attractive points to improve the negatively charged PZS polymer deposited on cationic surfactant TEA + ‐modified cores [30a,e–g]…”
Section: Resultsmentioning
confidence: 99%
“…Such carbon coating is widely employed to promote the property of electrode materials in an electrochemical field and to protect the stability of active core materials in catalysis . Moreover, if the organic coating contains heteroatoms, it can react with core materials to form other functional nanostructured materials [30a]. However, only very few organic coating materials have been mentioned in the previous reports.…”
Section: Introductionmentioning
confidence: 99%
“…The polymer served as a source for C, N, P, and S. The ZIF‐ 67 core is shown to be vital for the catalytic performance, as it plays the following roles: (1) it behaves as a structural template for the PZS coating and hence helps maintain the structural integrity of the hollow carbon shell during the pyrolysis process; (2) the MOF aids in the generation of a mesoporous structure, increasing the surface area of NPS‐HCS through the release of gases during the ZIF‐67 decomposition; (3) the MOF increases the amount of N‐doping, optimizing the distribution of nitrogen species in the final NPS‐HCS structure; (4) the MOF improves the wettability of the NPS‐HCS in water; (5) the cobalt species in the ZIF‐67 also promotes the graphitization of the carbon, which is vital for high selectivity. The latter was supported by an additional experiment which showed that if the catalysts cores consist of mixed metal MOFs (ZnCo‐ZIFs) or only Zn (such as ZIF‐8), the resulting carbons could not achieve the same catalytic activity as NPS‐HCS due to limited graphitization …”
Section: Mof‐derived Catalystsmentioning
confidence: 96%
“…2019,25,[2161][2162][2163][2164][2165][2166][2167][2168][2169][2170][2171][2172][2173][2174][2175][2176][2177][2178] www.chemeurj.org ing carbons could not achieve the same catalytic activity as NPS-HCS due to limited graphitization. [81]…”
Section: Metal-free Carbon Catalystsmentioning
confidence: 99%
“…Herein, we proposed a rational design to synthesize ultrafine S-doped RuP nanoparticles (<5 nm) embedded in a N,P,S-codoped carbon sheet matrix (S-RuP@NPSC) by using the multifunctional highly cross-linked polymer poly(cyclotriphosphazene-co-4,4′-sulfonyldiphenol) (PZS), which is one of the important members of the cyclophosphazene polymers. [34][35][36][37][38] The PZS possessed abundant N P, S O bonds and functional groups, which have great master in bonding metal ions and limiting the abnormal growth of nanoparticles. More importantly, the PZS with multiple elements of C, N, P, S in the same molecular structure was an ideal model to study the bonding process and reaction mechanism between Ru and C, N, P, S during the pyrolysis process.…”
Section: Introductionmentioning
confidence: 99%